Turning moss into algae: Prenylation targets in Physcomitrella patens - Antimisiaris, Marika F (Landes Bioscience, 2014)
Prenylation is a series of lipid posttranslational modifications that are involved in several key aspects of plant development. We recently knocked out every prenylation subunit in Physcomitrella patens. Like in Arabidopsis, knockout of protein farnesyltransferase and protein geranylgeranyltransferase in P. patens does not result in lethality; however, effects on development are extensive. In particular, the knockout of protein geranylgeranyltransferase results in small unicellular plants that resemble algae. Here we perform an analysis of predicted geranylgeranyltransferase target proteins in P. patens, and draw attention to those most likely to play a role in the knockout phenotype.